Angelica sinensis in China-A review of botanical profile, ethnopharmacology, phytochemistry and chemical analysis. (22nd August 2016) - Wei, Wen-Long; Zeng, Rui; Gu, Cai-Mei; Qu, Yan; Huang, Lin-Fang
Abstract: Ethnopharmacological relevance: Angelica sinensis (Oliv.) Diels, known as Dang Gui (in Chinese), is a traditional medicinal and edible plant that has long been used for tonifying, replenishing, and invigorating blood as well as relieving pain, lubricating the intestines, and treating female irregular menstruation and amenorrhea. A. sinensis has also been used as a health product and become increasingly popular in China, Japan, and Korea. Aim of the review: This paper aims to provide a systemic review of traditional uses of A. sinensis and its recent advances in the fields of phytochemistry, analytical methods and toxicology. In addition, possible trends, therapeutic potentials, and perspectives for future research of this plant are also briefly discussed. Materials and methods: An extensive review of the literature was conducted, and electronic databases including China National Knowledge Infrastructure, PubMed, Google Scholar, Science Direct, and Reaxys were used to assemble the data. Ethnopharmacological literature and digitalised sources of academic libraries were also systematically searched. In addition, information was obtained from local books and The Plant List (TPL, www.theplantlist.org). Result: This study reviews the progress in chemical analysis of A. sinensis and its preparations. Previously and newly established methods, including spectroscopy, thin-layer chromatography (TLC), gas chromatography (GC), high-performance liquid chromatography (HPLC), ultra-performance liquid chromatography(UPLC), and nuclear magnetic resonance analysis (NMR), are summarized. Moreover, identified bioactive components such as polysaccharides, ligustilide and ferulic acid were reviewed, along with analytical methods for quantitative and qualitative determination of target analytes, and fingerprinting authentication, quality evaluation of A. sinensis, and toxicology and pharmacodynamic studies. Scientific reports on crude extracts and pure compounds and formulations revealed a wide range of pharmacological activities, including anti-inflammatory activity, antifibrotic action, antispasmodic activity, antioxidant activities, and neuroprotective action, as well as cardio- and cerebrovascular effects. Conclusions: Within the published scientific literature are numerous reports regarding analytical methods that use various chromatographic and spectrophotometric technologies to monitor various types of components with different physicochemical properties simultaneously. This review discusses the reasonable selection of marker compounds based on high concentrations, analytical methods, and commercial availabilities with the goal of developing quick, accurate, and applicable analytical approaches for quality evaluation and establishing harmonised criteria for the analysis of A. sinensis and its finished products. Compounds isolated from A. sinensis are abundant sources of chemical diversity, from which we can discover active molecules. Thus, more studies on the pharmacological mechanisms of the predominant active compounds of A. sinensis are needed. In addition, given that A. sinensis is one of the most popular traditional herbal medicines, its main therapeutic aspects, toxicity, and adverse effects warrant further investigation in the future. Graphical abstract: